Architecture and dynamics of an A-kinase anchoring protein 79 (AKAP79) signaling complex. - Gold, MG; Stengel, F; Nygren, P; Weisbrod, C; Bruce, J; Robinson, C; Barford, D; Scott, J (2011)
A-kinase anchoring protein 79 (AKAP79) is a human anchoring protein that organizes cAMP-dependent protein kinase (PKA), Ca(2+)/calmodulin (CaM)-dependent protein phosphatase (PP2B), and protein kinase C (PKC) for phosphoregulation of synaptic signaling. Quantitative biochemical analyses of selected AKAP79 complexes have determined the quaternary structure of these signaling complexes. We show that AKAP79 dimerizes, and we demonstrate that, upon addition of a lysine-reactive cross-linker, parallel homomeric dimers are stabilized through K328-K328 and K333-K333 cross-links. An assembly of greater complexity comprising AKAP79, PP2B, a type II regulatory subunit fragment (RII 1-45) of PKA, and CaM was reconstituted in vitro. Using native MS, we determined the molecular mass of this complex as 466 kDa. This indicates that dimeric AKAP79 coordinates two RII 1-45 homodimers, four PP2B heterodimers, and two CaM molecules. Binding of Ca(2+)/CaM to AKAP79 stabilizes the complex by generating a second interface for PP2B. This leads to activation of the anchored phosphatases. Our architectural model reveals how dimeric AKAP79 concentrates pockets of second messenger responsive enzyme activities at the plasma membrane.